Efficacy of plant essential oils for repelling against American cockroach adults (Periplaneta americana L.) - Passara, H.; Soonwera, M.; Arhamad-Armeen, N.; Sittichok, S.; Jintanasirinurak, S. (My University, 2025)
The combination of four plant essential oils (EOs) from star anise, citronella grass, lemon grass, and cinnamon was evaluated for repelling American cockroaches by the dual-choice method. A combination of star anise + citronella grass had a repellency rate of 95%. In contrast, combinations of star anise + lemon grass and star anise + cinnamon were effective between 73% and 69%, but the synthetic chemical repellent (12% DEET) was less effective at 59%. Therefore, the essential oils formulae had a high potential for effective use and, further, are harmless for healthiness and the environment. Thus, they can replace more toxic synthetic insecticides.
Keywords: American cockroach; Cinnamon; Citronella grass; Lemon grass; Star anise